Management of Digital Marketing of Halal Products: Solutive Strategies for Empowering MSME Entrepreneurs - Ratnasari, Anne; Maryani, Anne; Yuniati, Yenni; Sofyan, Aning (KnE Social Sciences, 2024)
The Cekaz K1 business community is one of the business communities of micro, small, and medium enterprises (MSMEs) in Bandung Regency, West Java, Indonesia. This article results from research on digital marketing management training for halal products as a solution strategy for differentiating MSME business owners. The research aims to analyze forms of digital marketing and information on halal products to empower businesses. The research method used is descriptive to measure research phenomena carefully. Data collection techniques in the form of literature studies, interviews, and a research questionnaire were conducted by distributing it to the training participants, as many as 29 people. The sampling technique was conducted through a census; therefore, all training participants became research respondents. The study results show that business owners have a high knowledge of digital marketing content in serving advertisements that contain accurate, timely, complete product information, and sale promotions in the form of discounts, free shipping, and bonuses for customers who purchase many products. Business owners have a lot of knowledge about halal products, and the product information contains information about maintaining a healthy body and facts. Halal product information guides business owners in preparing and making promoted products to customers. Keywords: digital marketing, empowering halal products, MSME business owners